The Relationship Between Self-Confidence And Parents' Support With Students' Self-Regulation At Smp It Ad Durrah - Husna Sy , Hafizhatul; Hasanuddin, Hasanuddin; Darmayanti , Nefi (International Journal of Science, Technology & Management, 2023)
Apart from self-confidence, another factor that influences self-regulation is parental support. Parental support is to support children's lives, both in social, psychological and educational development. The aim of this research is to analyze the relationship between self-confidence and parental support with students' self-regulation at Ad-Durrah IT Middle School. The research results show that there is a relationship between self-confidence and parental support and self-regulation. This is shown by the coefficient F reg = 111.949 with p < 0.05, and the correlation coefficient R = 0.705 with p < 0.05, meaning that there is a positive relationship between parental confidence and support and self-regulation, the more positive the self- confidence and parental support, the higher self-regulation of SMP IT Ad Durrah students. Likewise with the value of the determinant coefficient (R2) which has a value of 0.497, which means that student self-confidence and the support of the student's parents contribute 49.7% to the self-regulation of SMP IT Ad Durrah students. At the time of entering adolescence, individuals begin to search for identity, so they want to have the opportunity to be able to regulate themselves and develop themselves . Apart from self-confidence, another factor that influences self-regulation is parental support. Parental support is to support children's lives, both in the social, psychological, and educational development fields . The aim of this research is to analyze the relationship between self-confidence and parental support with students' self-regulation at Ad-Durrah IT Middle School. The research results show that there is a relationship between self-confidence and parental support and self-regulation . This is indicated by the coefficient F reg = 111,949 with p < 0.05, and the correlation coefficient R = 0.705 with p < 0.05, meaning that there is a positive relationship to self-confidence and parental support with self-regulation, the more positive self-confidence and parental support, the higher the self-regulation Ad Durrah IT Middle School student . Likewise, the value of the diterminant coefficient (R2 ) has a value of 0.497, meaning that self-confidence students and the support of the students' parents contributed 49.7 % to self-regulation Ad Durrah IT Middle School student .